Childish fears - Gubaidullina F. R. (Preschool education: experience, questions and future development, 2016)
the paper dicusses the problem of childish fears, examines the types fears. The author points out that it is very important for grown-ups to pay attention to excessive fearfullness of children, excessive mpressionability that need to apply special upbringing influence.
Keywords: дети дошкольного возраста; эмоциональное развитие; детские страхи; preschool children; страхи; emotional development; childish fears; fears